Bassline composition for alternative rock using SP and SDS algorithms, a multi-objective approach (2016)
This research proposes a solution to the problem of finding a "good" bassline to accompany a melody and a drumbeat following the structure of the alternative rock genre. The solution method is made up of different steps which include: determining the key of the song by using a matching algorithm that compares the notes in the melody with the notes in each key, fitting chords to the melody by constructing a graph of possible progressions using candidate chords selected through a matching algorithm and finding the shortest path in it, improvising basslines using these chords as guidelines through the use of stochastic diffusion search algorithm. Solutions must satisfy constraints regarding their relationship with the drumbeat and the melody while maximizing the quality of the overall sound measured with two independent